TRANS-RESVERATROL CONTENT IN VITIS VINIFERA L CULTIVATED IN THE SÃO FRANCISCO RIVER VALLEY - BRAZIL AND POSSIBLE USE AS A FUNCTIONAL INGREDIENT IN FOODS - Lima, Rosa Helena Andrade Honorio; Vieira, Ícaro Gusmão Pinto; Mendes, Francisca Noélia Pereira (Seven Editora, 2025)
The trans-resveratrol is a polyphenol not flavonoid present in grape, especially in the skin and many studies proved its efficiency in human health. That is why there is a huge necessity of quantifying it in skins of grapes in nature consumed by the population. The proposal of this study was to quantify the content of trans-resveratrol by High-Performance Liquid Chromatography – HPLC in the skins of varieties (Vitis vinifera L) cultivated in the Northeast region of Brazil, in the São Francisco River valley in 2024 and propose the development of a functional ingredient obtained from these skins. The varieties analyzed were: “Red globe”; “Rubi”; Italia” and Patricia” bought in a Central market. After manual separation of the skin, pulp and seed, drying and the extraction of the active components of the skin, the latter was analyzed by HPLC. The major contents found were in the varieties" Rubi"(28,14ppm) and “Red Globe” (27,59ppm) followed by lesser values in ”Patricia” (14,97ppm) and "Italia"(3,77ppm) suggesting that the red coloration indicates a bigger quantity of trans-resveratrol. Comparing with the values obtained in the literature it was observed that in the skins of red grapes produced in the Valley of São Francisco have content of resveratrol equivalent or superior to grapes produced in other regions of the world. The levels of resveratrol can be sufficient to use them as functional ingredients, aggregating value to the residue of food processing. These discoveries reinforce the importance of investigating the composition of skins of grape from the São Francisco Valley and its relevance to the food industry and for the consumption as a source of trans-resveratrol. DOI: https://doi.org/10.56238/sevened2025.021-077